1987
DOI: 10.1042/bj2410229
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of meprin, a membrane-bound metalloendopeptidase from mouse kidney

Abstract: Meprin is an intrinsic protein of the brush border, a specialized plasma membrane, of the mouse kidney. It is a metalloendopeptidase that contains 1 mol of zinc and 3 mol of calcium per mol of the 85,000-Mr subunit. The enzyme is isolated, and active, as a tetramer. The behaviour of the enzyme on SDS/polyacrylamide gels in the presence and absence of beta-mercaptoethanol indicates that the subunits are of the same Mr (approx. 85,000) and held together by intersubunit S--S bridges. Eight S-carboxymethyl-L-cyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…Both proteases have extended binding sites and prefer substrates of at least 6 amino acids (Ref. 28 and Table V). The different specificities of the two subunits implicate diverse functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both proteases have extended binding sites and prefer substrates of at least 6 amino acids (Ref. 28 and Table V). The different specificities of the two subunits implicate diverse functions.…”
Section: Discussionmentioning
confidence: 99%
“…The Hydrolytic Efficiency of Meprin B Is Dependent on Peptide Length-Previous work indicated that meprin A has a preference for substrates with a minimum of eight amino acids (28). To test the peptide length requirement for efficient hydrolysis by meprin B, derivatives of sCCK8 NH2 were used as substrates (Table V).…”
mentioning
confidence: 99%
“…Zinc has been established as the active site metal in meprin A (1.1 mol z i n c h o l subunit), astacin (0.97 k 0.03 mol zinc/mol protein), and HCEILCE (approximately 1.3 pg/mg protein) (Butler et al, 1987;Stocker et al, 1988;Yasumasu et al, 1989aYasumasu et al, , 1989b. Reactivation studies have indicated that Zn2+, Cu2+, and Co2+ can reactivate astacin apoenzyme; Zn2+, and Cu2+ can reactivate the fish enzymes and meprin A apoenzyme (Wolz & Bond, 1995).…”
Section: Metal Requirementsmentioning
confidence: 99%
“…2B). Like astacin, meprin A has a considerably lower pI (4-5) (Butler et al 1987) than the bulk of the peptidases in SDF. It remains to be established which peptidases, by the designations used in this paper, correspond to the four Argiope peptidase fractions (A-D) of Kavanagh (1979) and Kavanagh and Tillinghast (1983), and in particular to the apparently homogeneous Argiope protease B and Argiope protease D. Similarities with respect to molecular mass, pI, and relative abundance make it likely that p16 is one of these two peptidases.…”
Section: Sdf Peptidasesmentioning
confidence: 99%